Acute disseminated encephalomyelitis associated with positive voltage gated potassium channel complex antibody - Kalakatsios, M; Hacohen, Y; Siddiqui, A; Dlamini, N; Vincent, A; Lim, M (2013)
Voltage gated potassium channel (VGKC) complex antibodies are associated with encephalopathies both in adult and children. The incidence of antibodies in the central nervous system demyelinating disorders is increasingly reported although their direct pathogenic role remains to be evaluated, with the exception of Aquaporin 4 antibodies. Here we describe a case of a 28 month old boy presenting with acute disseminated encephalomyelitis, with positive VGKC-complex antibodies and low sodium levels. He was treated with steroids and made a clinical and radiological recovery with normalisation of antibody levels. © 2012 Elsevier B.V. All rights reserved.